Lessons Learned from an Audit: Are You Being Fiscally Responsible? - Ernie M. Hills (Academic Chairpersons Conference Proceedings, 2016)
Department chair job descriptions often include the words “fiscal responsibility;” but what does that really mean? Having survived an extensive audit, the presenter will lead participants to consider best practices (and some that were not so good) in overseeing financial matters for an academic unit.
Keywords: Finances; management; legal issues; budgeting; dealing with external auditors